Formation of the Institute of Human Rights in Russia: Historical Aspects and Modernity - MELNIKOV, Viktor Yu.; KOLESNIKOV, Yuri A.; KISELEVA, Alla V.; DZHAMALOVA, Bika B.; NOVITSKAYA, Aleksandra I. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
Without understanding the past can be neither a viable present and no decent future. The appeal of the nation to its history – this is not an attempt to escape from the present and uncertainty about the future. This understanding of who we are, where we came from. Based on our experience, we can confidently move forward. Not happen in the Russian revolution, which way went the history of the world? Can we learn from the past to prevent another disaster? The lessons of history are there – they just need to be able to retrieve. The main lesson we can learn from what happened in 1917 – the need to value human life. Russia of the late XIX – early XX century was an incredible human potential.